Development and investigation of epoxypolyurethane composites with poly-3-hydroxybutyrate for stomatology - Galatenko, N.A.; Astapenko, Ye. S.; Kulesh, D.V.; Levenets, Ye.G.; Rozhnov, A. S. (Reports of the National Academy of Sciences of Ukraine, 2015)
A row of epoxypolyurethane (EPU) composites with various contents of poly-3-hydroxybutyrate (PGB) is obtained. The quantity of PGB in compositions was from 0.1 to 3.0% (mass). It is established that the tensile strength of composite materials changes not linearly and depends on the concentration of PGB. The EPU composition containing 0.1% (mass) of PGB has a maximum tensile strength of 23.0 MPa. The introduction of PGB to the composition leads to an increase in the relative elongation by 10–30%. According to IR-spectroscopy, the PGB introduction to the structure of EPU leads to changes in the polymer structure due to the formation of intermolecular hydrogen bonds between hydroxyl and amine groups of the EPU matrix and the ester groups of PGB. The investigated epoxypolyurethane composites with PGB are biocompatible and have to be recommended for the creation of new biologically active bone implants for stomatology.